2004
DOI: 10.1016/j.ergon.2004.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal symptoms in cold exposed and non-cold exposed workers

Abstract: A cross-sectional epidemiologic study was carried out to explore the relationship between musculoskeletal symptoms and cold exposure in a large meat processing company in Colombia. All workers in the packing areas (n=162) were recruited: 50 workers from very cold areas (+2 C) and 112 workers from less severely exposed areas (range +8 C to +12 C). Thermal environmental conditions were measured in both areas. By Standardized Nordic Questionnaire, there was a high prevalence of musculoskeletal symptoms among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 14 publications
(20 reference statements)
2
59
0
2
Order By: Relevance
“…Three studies relate MSD symptoms with exposure to low temperatures suffered by workers in cold-storage rooms: Piedrahita et al [115], Dovrat and Katz-Leurer [120], and Piedrahita et al [123]. The results reinforce the hypothesis that workers in cold environments have a higher risk of lumbar pain, and the prevalence of MSD is related to cold.…”
Section: Manufacturing Industry Of Food Productssupporting
confidence: 76%
“…Three studies relate MSD symptoms with exposure to low temperatures suffered by workers in cold-storage rooms: Piedrahita et al [115], Dovrat and Katz-Leurer [120], and Piedrahita et al [123]. The results reinforce the hypothesis that workers in cold environments have a higher risk of lumbar pain, and the prevalence of MSD is related to cold.…”
Section: Manufacturing Industry Of Food Productssupporting
confidence: 76%
“…The Swedish regulations, which also are valid within the European Union, state that while cutting meat, room temperature shall be no greater than 12°C and meat temperature no greater than 7°C [13]. This environmental issue was addressed by Pidrahíta, Punnett and Shahnavaz [14]. In this study it was shown that abattoir workers exposed to lower environmental temperatures had a higher prevalence of musculoskeletal symptoms, especially for low back, neck and shoulders.…”
Section: Introductionmentioning
confidence: 89%
“…Piedrahita et al performed a cross-sectional study in a large meat processing company in Colombia, using the Standardized Nordic Questionnaire. They found a high prevalence of MSS among workers in very cold areas (28C), especially for low back, and neck and shoulder pain, compared to workers exposed to less cold areas (8-128C) [Piedrahíta et al, 2004].…”
Section: Introductionmentioning
confidence: 99%